Effect of Feeding Slow Release Non Protein Nitrogen Sources on Performance of Dairy Cows - U, Manju G; N, Nagalakshmi D; V, Nagabhushana V; M, Venkateswarlu M; N, Rajanna N (Indian Journal of Dairy Science, 2022)
A study of 90 days duration was conducted on 18 multiparous crossbred cows (363Â±14kg, body weight; in II or III lactation; 3,000-4,500kg milk yield per lactation) randomly allotted to 3 dietary treatments with 6 animals in each group in a completely randomized design to investigate the effect of two slow release non protein nitrogen (SRNPN) products on feed intake, milk yield, milk composition, blood biochemical parameters and cost economics. The concentrate mixture for control group was formulated with maize, gram husk, ground nut cake, wheat bran, deoiled rice bran, salt and mineral mixture. The other two experimental concentrate mixtures were prepared by totally replacing ground nut cake with calcium salts of fatty acid coated urea (CFCU) and Hydroxypropyl methylcellulose coated urea (HMCCU) at 2.42%. The cows were offered fixed quantity of Napier green fodder (10kg/cow/day) and ad libitum paddy straw. The daily allowance of respective concentrate mixture offered to each cow was calculated based on body weight, previous week milk yield and roughage intake to meet the nutrient requirements of as per ICAR (2013). Incorporation of either of the coated urea products in concentrate mixtures did not affect the total DM intake, milk yield (13.94 to 14.11kg/d), milk composition (Milk fat, Protein, SNF and Lactose) and blood biochemical (Blood urea nitrogen, Glucose and total protein). Though non significant, the average daily cost of feeding (Rs/d) was lowered in CFCU (228.14) and HMCCU (215.98) diet fed cows compared to control group cows (237.08) by 3.77 and 8.89% respectively. Whereas, the cost of feeding (Rs) per kg milk production differed significantly (P